PATRIARCHAL IDEOLOGY IN WORKS OF VISUAL ART OF BALINESE CONTEMPORARY WOMEN ARTISTS - Hardiman, Hardiman; Putra, I Nyoman Darma; Atmadja, Nengah Bawa; Mudana, I Gede (E-Journal of Cultural Studies; Volume 11, Number 3, August 2018DO - 10.24843/cs.2018.v11.i03.p01, 2018)
Human problems are faced faced by Indonesian contemporary visual artists. However, the most typical are the problems faced by contemporary women visual artists, including those faced by Balinese contemporary women visual artists. Other than social problems, their personal problems also arise as women visual artists amidst patriarchal cultural construction. Balinese contemporary women visual artists, like Indonesian contemporary visual artists, are facing social problems and their personal problems as women. But, Balinese contemporary women visual artists also face very strong patriarchal ( purusa ) cultural ideology. This study aimed at revealing and describing the form of the subject matter of woman’s body as an expression of opposition in the works of visual art of the Balinese contemporary women visual artists; revealing and describing ideologies that operate behind the sexual representation of the Balinese contemporary women visual artists  and revealing and describing the contestation of meaning in the ideological sexual representation of Balinese contemporary women visual artists. This study using interpretive qualitative method produced, first , works of Balinese contemporary women artists which have traditional visual elements comprising contour, repetition, rythm, dialect. The works of Balinese contemporary women visual artists also have modern visual elements comprising spatial awareness,distortion, stylization, material character, unity, and personal identity. In addition, the works of Balinese contemporary women artists also have post-modern visual elements of trans-aesthetics, dialogism, and disorder. Secondly, the ideologies that operate behind the works of Balinese contemporary visual artists can be classified into three ideologies based on the forms and contents of the works of art. The ideologies are patriarchal ideology that is related to the theme of superiority,phallus symbol, and weak group; feminism ideology that is related to the theme of subordination, equality, and subjectivity construction, and aesthetical ideology concerning with style, which is related to the classification of styles based on time, place, form, technique, and subjject matter. Third , meanings which can be developed from Balinese contemporary women visual artists are the meaning of domestic body and the meaning of open body in the sexual representation of Balinese contemporary women artists. The meaning of domestic body is found in the works of Cok Mas Asiti, Ni Nyoman Sani, and Sutrisni. Sani while the meaning of open body in the works of IGK Murniasih and Nia Kurniati Andika.